Assessing the impact of the Covid-19 pandemic and the war in Ukraine on the performance of TSL companies listed on the WSE and NewConnect - Maciej Leszek HYZY; Ewa SPIGARSKA (Communications of International Proceedings, 2025)
The main motive behind the study was the authors’ expectations to examine how the Covid – 19 pandemic and the war in Ukraine have affected the TSL industry (transportation - freight forwarding - logistics), which is considered a barometer of the economy. To date, there has been no study in Poland explicitly devoted to examining the impact of the crisis caused by the COVID-19 pandemic and the war in Ukraine on the TSL industry. Therefore, this article partially fills a research gap. The subjects of the study were revenues, net profits, annual reports of companies listed on the Warsaw Stock Exchange, covering the logistics sector. All (a total of 6) annual financial reports of companies listed on the Stock Exchange covering the transportation and logistics sector and all reports/reports (a total of 6) of companies in the transportation and logistics sector listed on NewConnect were examined. The method used was to analyze the full versions of the narrative sections of the annual separate and consolidated financial statements. Auditor's audit reports and entity reports were analyzed. The research shows that the Covid-19 pandemic and the war in Ukraine have had both positive and negative impacts on the sectors analyzed, depending on the type of business. The results obtained do not take into account the impact of inflation on the categories shown in nominal terms, so where possible selected indicators were calculated, allowing a more realistic assessment of the industry under study. JEL: G01, G11, M21, M29, M49, O16
Keywords: financial and market indicators; COVID-19 crisis and pandemic; T-industry